•I am having trouble figuring out this question. Why is (3x + 5) (x - 2) + (2x - 3) (x - 2) not in factored form? Show specifically how to find the correct final factored form. What is this factoring method called?
Please help. Thank you.
3 answers
(x-2) is common in both terms so you can take that out as a factor.
(3x + 5) (x - 2) + (2x - 3) (x - 2) is partially factored
to finish ...
= (x-2)(3x+5 + 2x-3)
= (x-2)(5x+2)
to finish ...
= (x-2)(3x+5 + 2x-3)
= (x-2)(5x+2)
What I got waas (x-2)(5x+2). Is this right? What would I call this method? Is it distribution?